2009
DOI: 10.1002/etep.310
|View full text |Cite
|
Sign up to set email alerts
|

Damping torque analysis for DC bus implemented damping control

Abstract: -Damping torque analysis is a well-developed technique for understanding and studying power system oscillations. This paper presents the applications of damping torque analysis for DC bus implemented damping control in power transmission networks in two

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…By using the approach based on the graphical explanation, it is analytically concluded that in the multi-machine power system, STATCOM voltage control contributes no damping to the power system oscillation. Thus the same conclusion obtained and proved in References [7,8] for the SVC and STATCOM voltage control in single-machine infinite-bus power systems is established mathematically in this paper in the more general case of multi-machine power systems. In the paper, a method similar to the phase compensation method is proposed based on the graphical explanation of the DTA for the design of STATCOM stabilizer in the multi-machine power system.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…By using the approach based on the graphical explanation, it is analytically concluded that in the multi-machine power system, STATCOM voltage control contributes no damping to the power system oscillation. Thus the same conclusion obtained and proved in References [7,8] for the SVC and STATCOM voltage control in single-machine infinite-bus power systems is established mathematically in this paper in the more general case of multi-machine power systems. In the paper, a method similar to the phase compensation method is proposed based on the graphical explanation of the DTA for the design of STATCOM stabilizer in the multi-machine power system.…”
Section: Discussionsupporting
confidence: 75%
“…In the case of singlemachine infinite-bus power system, References [7] and [8] has provided a theoretical proof respectively that SVC and STATCOM voltage control contributes little damping torque by using the DTA. Here from Equation (12), it can be seen that STATOM voltage control provides the forced variation of active power delivered along the transmission line in the multi-machine power system to be proportional only to Du.…”
Section: Linearization Of the Above Equation Givesmentioning
confidence: 98%
See 1 more Smart Citation
“…This is quite similar to the voltage control function of a static Var compensator (SVC) or static synchronous compensator (STATCOM). The previous study has confirmed that the voltage control function of the SVC and STATCOM has little effect on the damping of power system oscillations [16–20].…”
Section: Dta For a Grid‐connected Dfigmentioning
confidence: 94%
“…With supplementary controllers, flexible alternating current transmission system (FACTS) devices can also be used to enhance the damping of low‐frequency power oscillations. Through the modulation of bus voltage, the phase shift between buses, and transmission line reactance, FACTS devices show promising results in enhancing both the dynamic and static performances of power systems .…”
Section: Introductionmentioning
confidence: 99%